Giant Gastric GIST Manifesting as Profound Iron Deficiency Anemia: A Case Report of a Diagnostic Pitfall - Suri Hanifa Efendi; Saptino Miro (HM Publisher, 2025)
Background: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract, yet they remain rare, particularly in patients under 40. Their clinical presentation is highly variable, often posing a diagnostic challenge. Severe anemia as the initial manifestation is common, but diagnostic confusion with benign lesions on initial biopsy is a significant clinical pitfall. Case presentation: A 39-year-old male presented with a three-month history of epigastric pain, early satiety, significant weight loss, and profound fatigue. His initial hemoglobin was a life-threatening 3.8 g/dL, consistent with profound iron deficiency anemia. Esophagogastroduodenoscopy (EGD) revealed a large, partially obstructing mass in the gastric corpus. However, initial endoscopic biopsies were paradoxically reported as a benign hyperplastic polyp. In contrast, contrast-enhanced computed tomography (CT) of the abdomen characterized a massive, 9.9 x 7.3 x 13.5 cm heterogeneously enhancing mass suggestive of malignancy. Given the stark discrepancy between imaging and histology, a decision was made for surgical intervention. The patient underwent a total gastrectomy. Final histopathological analysis of the resected specimen, supported by immunohistochemistry, confirmed a high-risk gastrointestinal stromal tumor with a high mitotic rate. Conclusion: This case underscores the critical importance of maintaining a high index of suspicion for GIST in patients with unexplained iron deficiency anemia, even in younger age groups. It highlights the potential for sampling error with endoscopic biopsies of large submucosal tumors, which can lead to dangerously misleading diagnoses. Clinicians must integrate clinical, radiological, and endoscopic findings to guide management, especially when histopathological results are incongruent with the overall clinical picture.